Potencial toxicológico e uso indiscriminado de antiparasitários em tempos de pandemia do SARS-CoV-2: Uma revisão narrativa: Toxicological potencial and indiscriminate use of antiparasitics at SARS-CoV-2 pandemic times: A narrative review (Health and Biosciences, 2022)
COVID-19 refers to a respiratory syndrome caused by SARS-CoV-2, an RNA virus with a high infectious-contagious character. In 2020, due to its worldwide transmission, was declared a pandemic by the World Health Organization. In the present study, a review was carried out, with the objective of evaluating the effectiveness and toxicity of antiparasitic drugs used to treat COVID-19. In this case, the following platforms were used as a research resource: SciELO, LILACS, PubMed, Google academic. Among the results, articles were identified on the pharmacological and toxicological mechanisms of action of the drugs: hydroxychloroquine, chloroquine, ivermectin and nitazoxanide, with a focus related to the fight against SARS-CoV-2. From the data, it was identified that the irrational use of these drugs can lead to cardiotoxicity, ototoxicity and hepatotoxicity, and the association of these drugs can trigger potentially toxic drug interactions. The strategy of using these antiparasitics was very important and very promising within the urgent search for drugs for the treatment and prophylaxis of a newly discovered disease. However, the available technical literature on their effectiveness and toxicity does not show scientific consistency to enable the safe use of these drugs for COVID-19. The high consumption of these drugs identified in 2020, the indication of excessive practice of self-medication and inappropriate off-label prescription indicate a serious problem in Brazilian public health, since the inappropriate use of hydroxychloroquine, chloroquine, ivermectin and nitazoxanide can put the user at risk for the development of intoxication or even worsening of the pathophysiology of the infection caused by the coronavirus.